ALTERATION OF SERUM TRANSAMINASES AND GAMMA GLUTAMYL TRANSFERASE IN HEAD AND NECK CANCER - DR ABHINANDAN BHATTACHARJEE; DR MD . NIZAMUDDIN KHAN; DR SARBANI GIRI; DR BANDANA TALUKDAR (International Journal of Pharma and Bio Sciences, 2016)
Although there are many studies on circulating tumor markers for breast cancer, germ cell tumors and adenocarcinomas of the colon, prostate and ovary, very few studies on the role of liver enzyme in head neck squamous cell carcinoma (HNSCC) and precancerous conditions are available. As various substances alter quantitatively in the serum during tumor development, we intended to explore the changes in serum aspartate transaminase (AST), serum alanine transaminase (ALT), serum gamma-glutamyl transpeptidase (GGT) and blood protein profile in these groups of patients. We examined these enzymes in histologically confirmed cases of SCC (n=31) and Premalignant lesions (n=30) of head and neck and found that AST, ALT. ANOVA results showed significant elevation of these enzymes in SCC and precancer conditions((p<.0001) . Moreover, mean serum GGT levels were also elevated in HNCA in comparison to control levels. We propose that determination of changes in serum AST, ALT and GGT in HNSCC and premalignant lesions may serve to predict malignant transformation or prognosis of such lesions which are otherwise clinically not always possible to ascertain.